Study of fire damaged concrete structure - Maslinda, Johanis (2012)
This study is under the field of Structural Forensic which is investigating the damages and any deterioration on concrete structure. This study is focused on the effect of fire temperature on concrete in terms of changes in colour, physical and strength of concrete. Based on the changes observed, the range of temperature that the concrete structure has been exposed can be identified. The temperature is identifying so that the damages of concrete can be classified into which class. After the class of damage is identified, the method of solution that suitable for a particular damage can be determined. This study is fully based on the literature review from sources such as journal, article etc. that have acknowledged the validity of the content and meet the stated purpose of the study. The methods that used for this study is literature review and analysis of literature. These both methodologies have few stages. The methodology of analysis is the important one because of the Analysis Chapter is the critical part of this study to develop results that fulfill the objectives outlined. From the comparison analysis of selected sources, the result is a summary table that could be use as a reference for solution any fire damaged cases. To prove the usable of that table, a real life case study is analyzed using that table created. The result from analysis is then comparing to the real solution that know from the interviewed to the involved company. This study was succeeded to develop one table that can use as a reference for temperature identifying that caused the damages on concrete. One of the methods to determine the damages on concrete is by observation.